Selenium and Selenoprotein P Deficiency Correlates With Complications and Adverse Outcome After Major Trauma - Braunstein, Mareen; Kusmenkov, Thomas; Zuck, Catrin; Angstwurm, Matthias; Becker, Niels-Peter; Böcker, Wolfgang; Schomburg, Lutz; Bogner-Flatz, Viktoria (Shock (Augusta, Ga.), 2020)
A declining selenium (Se) status constitutes a characteristic of critical illness and may affect disease course and survival. The dynamics of trauma-induced changes in biomarkers of Se status are poorly characterized, and an association with multiple organ failure (MOF) and mortality can be hypothesized. It was the aim of this study to investigate Se and selenoprotein P (SELENOP) concentrations in major trauma patients during the early posttraumatic period. Twenty-four patients after major trauma (ISS ≥16) were included at our level one trauma center. Se supplementation ever during the 90-day observation period was defined as an exclusion criterion. Serum samples were drawn within less than 60 min after trauma, and after 6 h, 12 h, 24 h, 48 h, and 72 h. Serum Se was analyzed by X-ray fluorescence and SELENOP concentrations by ELISA. The data were correlated to clinical parameters, occurrence of MOF defined by MOF and APACHE II score, lung injury defined by Horowitz index and clinical outcome (90-days survival). Serum Se and SELENOP concentrations of the trauma patients were significantly below the average of healthy European subjects (mean ±SD; Se, 41.2±8.1 vs. 84.7±23.3 μg/L, P < 0.001; SePP, 1.5±0.3 vs. 4.3±1.0 mg/L, P < 0.001). A strong deficit was present already at the first time point (Se; 33.6±10.5 μg/L, SELENOP: 1.4±0.5 mg/L). The clinical scores collectively showed an inverse relation between health status and Se biomarkers. Patients who did not survive the 90-day observation period exhibited significantly lower initial post-trauma Se status than the surviving patients (mean±SD; Se, 24.7±7.2 vs. 39.2±8.4 μg/L, P<0.05; SePP, 1.1±0.4 vs. 1.6±0.4 mg/L, P<0.05). Very low Se and SELENOP concentrations occur fast after major trauma and are associated with poor survival odds. These findings support the notion that early Se substitution may constitute a meaningful adjuvant treatment strategy in trauma patients.